The Prevalence of Dyslipidemia among Type 2 Diabetes Mellitus Patients in Al-khums Diabetic Center-Libya (Journal of Academic Research, 2024)
Background: An increase in the prevalence of diabetes mellitus has led to an increase in renal and cardiovascular complications. For this complication, dyslipidemia is a known risk factor.Objective: This study aimed to identify the prevalence and patterns of dyslipidemia in people with type 2 diabetes mellitus (T2DM) and to estimate the influence of clinical and lifestyle factors on dyslipidemia. Results: A high prevalence of dyslipidemia (61%) was found in people with T2DM. The most common lipid abnormality in our study was a low level of HDL-C followed by high TG and high LDL-C respectively. There was no statistical difference between males and females in lipid abnormalities. There was a significant association between poor diabetic control, BMI, smoking, and low physical activity with the occurrence of dyslipidemia.Conclusion: These studies indicate that dyslipidemia is a common complication of T2DM, with a high prevalence among T2DM patients. Control of diabetes mellitus, screening, and management of dyslipidemia will reduce the micro and macrovascular complications in T2DM patients.Keywords: diabetes mellitus, dyslipidemia. Lipid profile.